A Thousand Years Poured into the Present: Ecocritical Fictions in the Poetry of Suga Keijirô - Jorge, Julia (Universidad Pedagógica y Tecnológica de Colombia, 2022)
This paper approaches the poetic work of a contemporary Japanese poet, Keijirô Suga, from its resonances with the discussions of ecocriticism. It proposes the critical operator of ecocritical fiction that in the gesture of the interpretative reading of the poems and the theoretical reflection allows to identify these resonances. The journey finds temporary spaces configurations around the future, the landscape and the relationship between the human and the non-human. Thus the article contributes to the field of knowledge of contemporary Japanese poetry and ecocriticism. Finally, contemplating the theoretical reflection, we expose an ethical position distanced from certain environmentalist positions.